Modulation of the dual-faced effects of miR-141 with chitosan/miR-141 nanoplexes in breast cancer cells - (:unkn) unknown (WILEY, 2019)
Background miR-141, known as a tumor suppressive microRNA, is downregulated in breast cancer. However, recent contrasting studies report that it also acts as oncogene when it is upregulated. The present study aimed to investigate whether miR-141 is a tumor suppressor or oncogenic when it reaches normal levels in chitosan/miR-141 nanoplexes. Methods Chitosan nanoplexes were prepared using simple complexation method. Nanoplexes were characterized by a gel retardation assay and zeta potential and particle size measurements. To determine the expression level of miR-141, a quantitative real-time polymerase chain reaction was performed. The effects of miR-141 mimics were investigated with respect to angiogenesis by vascular endothelial growth factor (VEGF), epithelial-mesenchymal transition (EMT) by E-cadherin, metastasis by Igfbp-4 and Tinagl1 enzyme-linked immunosorbent assays, invasion by an invasion chamber, and apoptosis by Annexin V. Results The miR-141 expression levels of MDA-MB-231 and MDA-MB-435 cells by administration of chitosan/mimic miR-141 nanoplexes reached endogenous miR-141 levels of a non-tumorigenic epithelial breast cell line, MCF-10A. According to our results, metastasis, VEGF, EMT and invasion in breast cancer cells were diminished, whereas apoptosis increased by 1.5- and 2.4-fold in breast cancer cell lines as a result of the miR-141 mimics. Conclusions In conclusion, we have demonstrated that administration of miR-141 mimics at the determined doses to breast cancer cells revealed a tumor suppressor effect, and not the oncogenic face. The delivery of miR-141 by chitosan nanoplexes presents a promising approach for the suppression of breast cancer.
Keywords: breast cancer cells; chitosan nanoplexes; double-faced miRNA; miR-141; MICRORNA-200 FAMILY; PROLIFERATION; INVASION; METASTASIS; MIRNA-141; TARGETS; ROLES; GENE